CITIZEN SCIENCE PROJECT DESIGN FOR ECOLOGY COURSE: REDUCING POLLUTION CAUSED BY GOLD MINING - Susbiyanto, Susbiyanto; Hidayat, Topik; Surtikanti, Hertien Koosbandiah; Riandi, Riandi (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
The article aims to provide an overview of designing a citizen science project in ecological learning, focusing on the case of gold mining pollution in the Batanghari River area. This research employed a qualitative method, non-interactive type with the approach used being concept analytical. The design of the citizen science project is conducted through a sequential cycle with its main components including: identifying the need or problem, determining if citizen science is the right approach, designing the project, building the community, managing the data, and evaluating the project. This project design illustrates an organized method of citizen science in ecological learning that is customized to the gold mining area. The contribution of participants is very important to emphasise at every activity in the project design, therefore the development of activities in this project refers to the logic model. The type of project relevant to the issue raised is to assess the potential or ecological status of the Batanghari River through the measurement of biological quality elements, physico-chemical elements, and hydromorphological quality elements, referring to the European Environment Agency standards. The design incorporates two distinct components: a collaborative project model and a framework based on research, both of which are arranged into mini-project activities. As a result, the project will contribute to improving students' skills in monitoring and collaborating with communities, as well as accommodating ecological learning activities intended as actions to help mitigate the problem of pollution due to gold mining in the Batanghari River.